World Economic Outlook and International Capital Markets Interim Assessment, 1998. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1999)
This interim update of the IMF's latest regular reports on the World Economic Outlook (published in October 1998) and International Capital Markets (September 1998) provides a preliminary assessment of the unusual turbulence in international financial markets during much of the period August-November 1998, and its implications for the global economic outlook and for policy. The survey of prospects and policies is the product of a comprehensive interdepartmental review of world economic developments, which draws primarily on information the IMF gathers through its consultations with member countries. For its eveluation of developments in financial markets, the report also draws, in part, on informal discussions with commercial and investment banks, securities firms, stock and futures exchanges, and regulatory and monetary authorities.